ChemInform Abstract: Eosin Y Catalyzed Visible‐Light‐Driven Aerobic Oxidative Cyclization of Thioamides to 1, 2, 4‐Thiadiazoles. Issue 26 (6th June 2013) - Srivastava, Vishnu P.; Yadav, Arvind K.; Yadav, Lal Dhar S.
Abstract Notable features of the title method are a simple one‐pot operation, high efficiency, and eco‐friendly reagents.